Chinese yam (Dioscorea): Nutritional value, beneficial effects, and food and pharmaceutical applications. (April 2023) - Li, Ye; Ji, Shengyang; Xu, Tao; Zhong, Yongheng; Xu, Minghao; Liu, Yuqi; Li, Mingjun; Fan, Bei; Wang, Fengzhong; Xiao, Jianbo; Lu, Baiyi
Abstract: Background: Currently, balanced diet and healthy foods are attracting increasing attention due to their great health-beneficial effects. The tuber of Dioscorea (yam) is both edible and medicinal, as it contains various functional compounds with multiple pharmacological activities and disease targets. Moreover, yam tuber can serve as a vegetable or staple food due to its high starch content. Therefore, exploring the functional activities of yam tuber and its application in food and medicine industries is significant. Scope and approach: This review comprehensively summarizes the characteristics and application of yam tuber, as well as the findings about its primary nutrients, distinct functional components, extraction technologies, detection methods and biological activities, and provides some new prospects for further investigation. Besides, the development and comprehensive utilization of yam tuber products are elucidated. Finally, some future research directions for better utilization of yam tubers are suggested. Key findings and conclusions: The Dioscorea genus is distributed worldwide with a wide variety of species. Yam tuber is rich in nutrients and bioactive compounds, such as starch, protein, non-starch polysaccharides, steroid saponin, allantoin, and phenolic compounds. The most important health benefits include antioxidant activity, anti-inflammatory activity, gastrointestinal protection, gut microbiota regulation, cardiac diseases treatment, hypoglycemic activity, anti-tumor activity, and estrogen-like effect. We also summarize the applications of yam tuber in foods and medicine. Finally, the review indicates that better utilization of yam tuber is hindered by poor variety protection, limited research on its pharmacological activities, browning phenomenon, and some safety concerns. Graphical abstract: Image 1 Highlights: Yam is both a crop and a medicinal plant with many applications Yam tuber is a good source of high-quality starch. Their active compounds mainly include polysaccharide, allantoin, dioscin, polyphenols, etc. Yam tuber possess many beneficial effects and has great potential to be used in functional foods and medicines.